The influence of social comparison on purchase intention through fear of missing out and envy in Korean food in Langowan, North Sulawesi Indonesia - Tumiwa, Vini Gledis; Esti Susanti, Christina (Technium Social Sciences Journal, 2024)
This research aims to explore an in-depth understanding of the impact of social comparison on the intention to buy Korean food through fear of missing out (FOMO) and feelings of envy in the people of Langowan, North Sulawesi. The main aim of this research is to analyze the relationship between social comparison and purchase intention, paying attention to the role of two mediating variables, namely Fear of Missing Out (FOMO) and envy. Research data was obtained using a questionnaire. The final sample consisted of 200 respondents and the data analysis technique used in this research was SEM (Structural Equation Model) using LISREL as a data processing tool to test six hypotheses. The results of direct influence research prove that social comparison has a positive and significant effect on FOMO, FOMO has a positive and significant effect on buying intention, social comparison has a positive and significant effect on envy, envy has a positive and significant effect on buying intention. Meanwhile, the indirect effect is that social comparison has a significant effect on buying intention through FOMO and envy. The results of these findings provide practical guidance recommendations for marketers and food producers to develop effective marketing strategies to take advantage of social comparison, FOMO and envy which can trigger consumer purchasing intentions. These findings can also be used as a reference for micro, small and medium enterprises (MSMEs) in Langowan, North Sulawesi to sell Korean food products.